2008
DOI: 10.1111/j.1365-2133.2008.08451.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain during photodynamic therapy is associated with protoporphyrin IX fluorescence and fluence rate

Abstract: Pain during PDT was correlated with the PpIX fluorescence in the treatment area prior to illumination. Pain was reduced using a lower fluence rate during PDT of acne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
115
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(128 citation statements)
references
References 20 publications
9
115
3
1
Order By: Relevance
“…The interindividual difference in size might have biased the results by influencing the pain intensity [4,5]. However, other authors have already shown that the pain intensity is strongly dependent on the localization [2,4,6]. A cosmetic unit is easy to determine in clinical practice and subsumes both individual size and localization of the treated area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interindividual difference in size might have biased the results by influencing the pain intensity [4,5]. However, other authors have already shown that the pain intensity is strongly dependent on the localization [2,4,6]. A cosmetic unit is easy to determine in clinical practice and subsumes both individual size and localization of the treated area.…”
Section: Discussionmentioning
confidence: 99%
“…The main adverse effect in PDT treatment is pain. It has been shown that pain intensity depends on the localization [2,3], size [3,4,5], histological type [4], redness [5] and protoporphyrin IX (PpIX) fluorescence [6] of the treated lesion. Also different light sources [7,8,9], fluence rates [6] and photosensitizing agents [10,11] affect the pain additionally.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies [13,15,21], the aim of this work is to implement fluorescence imaging in a clinical protocol to improve the clinical outcome. In our multi-center clinical trial of PDT for skin cancer in Brazil, we have added three fluorescence measurements during PDT implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Even though this results in a slightly more shallow treatment due to the dominating absorbing features of PpIX in the blue wavelength range (figure 1 c) many efficient results have been reported. [5][6][7][8][9] Daylight has been shown to be associated with a lower experienced pain 10 and the preferred choice of treatment by the majority of patients. 3 In the work presented here we compare daylight PDT to conventional PDT where the artificial light source Aktilite is adopted (Akitlite, Photocure ASA, Norway 11 ).…”
mentioning
confidence: 99%